EFEKTIVITAS MODEL COOPERATIVE TYPE MAKE A MATCH TERHADAP HASIL BELAJAR IPAS MATERI METAMORFOSIS SISWA KELAS III SEKOLAH DASAR - Nurwahid; Desty Dwi Rochmania (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Learning models that are enjoyable can foster students' interest in learning and enhance their creativity and learning outcomes. The cooperative type make a match model is a learning model that encourages students to actively search for matching cards containing questions and answers, making learning more interactive and enjoyable. This study aims to: 1) determine the learning outcomes of third-grade students at SDN Diwek I Jombang on metamorphosis material before implementing the cooperative type make a match model; 2) determine the learning outcomes after implementing the model; and 3) determine the effectiveness of the cooperative type make a match model on student learning outcomes. This research uses a quantitative approach with a pre-experimental design type, specifically the One Group Pretest-Posttest Design. The sample consisted of 31 third-grade students selected through saturated sampling technique. Data were collected through tests (pretest and posttest) and documentation. Data analysis used descriptive statistical analysis, normality test with Shapiro-Wilk, hypothesis testing with Paired Sample T-Test, and effectiveness test with N-Gain. The results showed: 1) the average pretest score before treatment was 68.13; 2) the average posttest score after treatment increased to 87.87; 3) the Paired Sample T-Test obtained a significance value of 0.000 <0.05, indicating a significant difference between pretest and posttest results. The N-Gain test showed an average score of 0.6112 in the medium category or 61.12% in the quite effective category. Thus, it can be concluded that the cooperative type make a match model is effective in improving the learning outcomes of third-grade students on metamorphosis material at SDN Diwek I Jombang.